A rare case report of a saddle pulmonary embolism presenting with high grade fevers, responsive to anticoagulation. Issue 9 (March 2018) - Saad, Muhammad; Shaikh, Danial H.; Adrish, Muhammad
Abstract: Rationale: Pulmonary embolism can manifest by a myriad of clinical symptoms. High grade fever is a rare presentation of thromboembolic phenomenon. Patient concerns: A middle aged woman presented with high grade fevers. Diagnoses: Patient remained febrile despite broad spectrum antibiotics. All cultures were negative. CT angiogram of the chest was done, eliciting a large saddle embolus. Interventions: Intravenous tissue plasminogen activator (t-PA) was administered and subsequently started on anticoagulation. Patient became afebrile 3 days after initiation of anticoagulation and all antibiotics were discontinued. Outcomes: We demonstrate a case of a saddle pulmonary embolism presenting with high grade fevers that responded to anticoagulation. Lessons: It is imperative to include pulmonary embolism in the differential diagnosis, when presented with high-grade fever in patients with unclear diagnosis.